Research on Slovenian organs from the beginning of the twentieth century to the monograph Orgle Slovenije in 2018 - Dobravec, Jurij (Muzikološki zbornik, 2020)
The paper analyses the development of the structure and content of pipe organ catalogues that have appeared in Slovenian organology since the beginning of twentieth century. Of seventy catalogues describing multiple organs, particular attention is devoted to ten, especially the inventories of the Maribor (1911) and Ljubljana (1918) Dioceses, and the monograph Orgle Slovenije (2018).
Keywords: catalogue; database; katalog; organografija; organography; orgle; pipe organ; podatkovna zbirka; research history; Slovene musicology; Slovenija; slovenska muzikologija; zgodovina raziskav